Electrochemotherapy of tumours - Serša, Gregor (Radiology and oncology (Ljubljana), 2006)
Electroehemotherapy consists of chemotherapy followed by local application of electrie pulses to the tumour to increase drug delivery into cells. Drug uptake can be inereased by electroporation for only those drugs whose transport through the plasma membrane is impeded. Among many drugs that have been tested so far, only bleomycin and cisplatin found their way from preclinical testing to clinical trials. In vitro studies demonstrated several fold inerease of their cytotoxicity after electroporation of cells. In vivo, electroporation of tumours after local or systemic administration of either ofthe drugs, i.e. electrochemotherapy, proved to be an effective antitumour treatment. In preclinical studies on several tumour models, electrochemotherapy either with bleomycin or cisplatin was elaborated and parameters for effective local tumour control were determined. In veterinary medicine, electrochemotherapy also proved to be effective in the treatment of primary tumours in cats, dogs and horses. In human clinical studies, electrochemotherapy was performed on the patients with progressive disease andaccessible tumour nodules of different malignancies. All clinical studies demonstrated that electrochemotherapy is an effective treatment for local tumour control in cancer patients.
Keywords: Bleomicin; Bleomycin; Cisplatin; Drug Delivery Systems; Drug Therapy; Electroporation; elektrokemoterapija; Elektroporacija; Neoplasms; Novotvorbe; onkologija; Therapy; tumor; tumorji; Zdravilo, sproščanje, sistemi; zdravljenje